Internationalization of the entrepreneurial activity of social purpose organizations - Rafał Kusa (International Journal of Management and Economics, 2016)
The objective of this paper is to analyse and identify patterns of international entrepreneurial activity of social purpose organizations. The article utilizes international social entrepreneurship literature to develop an understanding of the international activity of social entrepreneurs and to identify factors that differentiate their activity. A cluster analysis was conducted to identify patterns of international social entrepreneurial activity, which included: the subject of activity, the types of beneficiaries, the scope of activity, and the legal type of organization. As a result, a survey sample of 55 international social ventures was divided into 3 homogeneous groups. The groups were (1) solution providers, (2) entrepreneurial charities, and (3) intermediaries. The results of the analysis show the diversity of the international activities of social entrepreneurs, although only a portion of them operate internationally. These findings contribute to a greater understanding of social entrepreneurs' motivation and the paths of their internationalization activity.
Keywords: L26; L31; 650; non-profit organization; social entrepreneur; internationalization; cluster analysis